Comparison of Efficacy and Safety Between Dronedarone and Amiodarone Used During the Blind Period in Patients with Atrial Fibrillation After Catheter Ablation - Li Y; Hu T; Lin M; Wang Q; Han W; Zhong J (Dove Medical Press, 2023)
Yihan Li,1 Tong Hu,1 Mingjie Lin,1,2 Qinhong Wang,1 Wenqiang Han,1 Jingquan Zhong1,2 1Department of Cardiology, Qilu Hospital of Shandong University, Jinan, Shandong Province, People's Republic of China; 2Department of Cardiology, Qilu Hospital (Qingdao), Cheeloo College of Medicine, Shandong University, Qingdao, Shandong Province, People's Republic of ChinaCorrespondence: Jingquan Zhong, Department of Cardiology, Qilu Hospital of Shandong University, Jinan, Shandong Province, People's Republic of China, Tel: +008618560086597, Email 198762000778@email.sdu.edu.cnBackground: Dronedarone is an effective drug for maintaining the sinus rhythm in patients with atrial fibrillation (AF). The efficacy and safety of dronedarone versus amiodarone in patients with AF after catheter ablation (CA) needs more evidence. We retrospectively compared the efficacy and safety of dronedarone and amiodarone in our hospital.Methods: Patients who underwent CA from January 2021 to January 2022 and used dronedarone (n=229) or amiodarone (n=202) during the blind period were enrolled. The recurrence of AF in post-and during the blanking period was compared between the groups; the rehospitalization for re-ablation and adverse drug events (ADE) were also calculated.Results: During an average follow-up period of 14.28 months, the long-term recurrence rate of AF did not differ significantly between the amiodarone group and dronedarone group (22.71% vs 21.29%, hazard ratio [HR], 1.033, 95% confidence interval [CI], 0.661- 1.614; p=0.888). The recurrence rate in the blanking period also showed no statistically significant differences between the amiodarone group and dronedarone group (9.90% vs 14.41%, HR, 0.851; 95% CI, 0.463- 1.564; p=0.604). The re-hospitalization rates for re-ablation between two groups did not differ between the amiodarone group and dronedarone group (4.65% vs 13.46%; p =0.144). The incidence of ADE was higher in the dronedarone groups than that in the amiodarone group (16.59% vs 5.45%, p < 0.001). The main adverse drug events in the dronedarone and amiodarone groups were gastrointestinal (6.99%) and bradycardia (2.48%), respectively.Conclusion: Compared to the amiodarone group, the dronedarone group had a similar blank-period and long-term recurrence rate of AF and a higher incidence of ADE.Keywords: atrial fibrillation, catheter ablation, amiodarone, dronedarone